Prediction of Liquid Magnetization Series Data in Agriculture Based on Enhanced CGAN - Nie, Jing; Wang, Nianyi; Li, Jingbin; Wang, Yi; Wang, Kang (Frontiers in Plant Science, 2022)
The magnetized water and fertilizer liquid can produce biological effect of magnetic field on crops, but its residual magnetic field strength is difficult to be expressed quantitatively in real time, and accurate prediction of it is helpful to define the scope of action of liquid magnetization. In this paper, a prediction model for liquid magnetization series data is presented. It consists of Conditional Generative Adversarial Network (CGAN) and Projected Gradient Descent (PGD) algorithm. Firstly, the real training dataset is used as the input of PGD attack algorithm to generate antagonistic samples. These samples are added to the training of CGAN as true samples for data enhancement. Secondly, the training dataset is used as both the generator and discriminator input of CGAN to constrain the model, capture distribution of the real data. Thirdly, a network model with three layers of CNN is built and trained inside CGAN. The input model is constructed by using the structure of two-dimensional convolution model to predict data. Lastly, the performance of the model is evaluated by the error between the final generated predicted value and the real value, and the model is compared with other prediction models. The experimental results show that, with limited data samples, by combining PGD attack with CGAN, the distribution of the real data can be more accurately captured and the data can be generated to meet the actual needs.